Hubungan Status Gizi, Pola Makan, Dan Kecemasan Terhadap Kejadian Hiperemesis Gravidarum Di Rumah Sakit Umum Andhika : The Relationship between Nutritional Status, Diet, and Anxiety on the Incident of Hyperemesis Gravidarum at Andhika General Hospital - Darmayanti, Erlina (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Hyperemesis gravidarum is a complaint of severe nausea and vomiting more than 10 times a day during pregnancy which can cause fluid deficiency, weight loss, or electrolyte disturbances thereby disrupting daily activities and endangering the fetus in the womb. The incidence of cases of hyperemesis gravidarum is 0,8% to 3,2% of all pregnancies or about 8 to 32 cases per 1000 pregnancies. Nutritional status, diet, and anxiety are factors that can influence the incidence of hyperemesis gravidarum in first-trimester pregnant women. This study aims to determine the relationship between nutritional status, diet, and anxiety with the incidence of hyperemesis gravidarum in Andhika General Hospital. Methods: This study uses a quantitative method of descriptive analytic design with a cross-sectional approach. The sampling technique used was total sampling with a total of 54 respondents. Results: The results showed that there was a significant relationship between nutritional status and the incidence of hyperemesis gravidarum which obtained a p-value of 0,004; dietary pattern and the incidence of hyperemesis gravidarum a p-value of 0,021; anxiety and the incidence of hyperemesis a p-value of 0,010. Discussion: This study concludes that there is a relationship between the variables of nutritional status, diet, and anxiety with the incidence of hyperemesis gravidarum at Andhika General Hospital in 2022. Advice for pregnant women can increase knowledge and understanding of tips for carrying out a healthy pregnancy that can be obtained through health workers and other information media improve nutritional status by improving diet according to the needs of pregnant women recommended by health workers such as consuming balanced nutrition (protein, carbohydrates, fat, minerals, and vitamins) during pregnancy.